MAPPING VOTES for VOTING GENERAL ELECTIONS MEMBERS of THE HOUSE REPRESENTATIVES, and REGIONAL HOUSE REPRESENTATIVES in SUKOHARJO SUB-DISTRICT, SUKOHARJO DICTRICT 2019 - Setiawan, Bowo; Sudargono, Agus; Rohsulina, Pranichayudha (Journal of Geography Science and Education, 2019)
This research aims to distribution of general voting pleaces member of the house of representative and regional people’s representative asembly on sukoharjo sub-district and sound calculation results political parties general election participants member of the house of representative and regional people’s representative assembly every pleace of voting votes in Sukoharjo sub-districtSukoharjo district’s. This report uses quantitative descritive that is disclosure and know the location point spreadsof general election places members of the house of representative and regional people’s representative assembly 2019. And resuilts of sound calculations every political party every place voting around sukoharjo sub-district, data colection techniques used are are through direct observation in te field,  and documentation data analysis techniques used are analysis of table and data map. This research results are spreadd of spot vocational places in sukoharjo sub-district. There are 252 sound vocational places spreads in 14 areas set by the commission of general elections accordingto many population in every way, the most amount of the most vocational place is Sukoharjo cheap and Gayam cheap each with 27 sound vocational place, and the little area of number of sound votes Combongan cheap with 13 sound vocation place general election member of the house of representative, in the level of the people’s representative of the republic of indo the provincial people’s representativf council and the district representative concil in the sukoharjo sub-district dominated by PDIP parties Keywords: distribution, voting place house of representative, regional people’s representatif assembly, Party